2000
DOI: 10.1002/1096-9071(200007)61:3<341::aid-jmv10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential detection of rhinoviruses and enteroviruses RNA sequences associated with classical immunofluorescence assay detection of respiratory virus antigens in nasopharyngeal swabs from infants with bronchiolitis

Abstract: To define the role of enteroviruses and human rhinoviruses as etiological agents in childhood bronchiolitis, clinical aspirates from 84 infants admitted to hospital with symptoms of obstructive bronchiolitis were tested by picornavirus RT-PCR assay, adenovirus PCR assay and classical immunofluorescence antigen detection of common respiratory viral agents. Respiratory syncytial viruses (A&B) were detectable in 45 of 84 (53.6%) nasopharyngeal aspirates from infants with bronchiolitis, whereas coronaviruses, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
46
2
12

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 24 publications
7
46
2
12
Order By: Relevance
“…4,5,7,15 In this study, RV was the second most common agent detected in the respiratory secretions (17% of cases) of infants hospitalized for AB, which is a frequency that is comparable with the studies mentioned. Furthermore, we have demonstrated that RV can be solely detected in infants with AB in the first months of life, as can be observed by the ages of the patients studied (median: 2 months of age).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…4,5,7,15 In this study, RV was the second most common agent detected in the respiratory secretions (17% of cases) of infants hospitalized for AB, which is a frequency that is comparable with the studies mentioned. Furthermore, we have demonstrated that RV can be solely detected in infants with AB in the first months of life, as can be observed by the ages of the patients studied (median: 2 months of age).…”
Section: Discussionsupporting
confidence: 84%
“…2,5,14,16 An association of infections by RV and RSV in infants has been demonstrated before. 4,5,7,14 Indeed, Papadopoulos et al 5 found an association between the presence of both agents with the severity of AB episodes. In this study we identified this combination in 4/6 cases of RV infection, corroborating the findings of Papadopoulos et al However, the restricted number of cases does not allow more detailed analyses of the association with severity of AB episodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With PCR methods, because it is difficult to design compatible multiplex primer sets (3), the maximum number of viruses detectable in a single assay is relatively small (2). Moreover, unambiguous viral identification with degenerate PCR often is complicated by the existence of highly homologous relatives, and discrimination between viral subtypes or genera requires additional labor-intensive procedures such as restriction enzyme analysis, sequencing, or hybridization blotting of the PCR product (4)(5)(6)(7)(8). Perhaps most significantly, even the broadest multiplexing is inherently biased, requiring assumptions that ultimately restrict the possible outcome to the selected candidate viruses.…”
mentioning
confidence: 99%